Is Embryo Cryopreservation Causing Macrosomia—and What Else? - Orvieto, Raoul; Kirshenbaum, Michal; Gleicher, Norbert (Frontiers in Endocrinology, 2020)
The number of embryos transferred during an IVF cycle is directly related to the high incidence of multiple births, which is the culprit of perinatal morbidity. Therefore, single fresh embryo transfer (ET) strategy, or freeze-all, followed by a single frozen-thawed embryo transfer (FET) cycle, may dramatically reduce the rate of multiple births, without compromising the cumulative live birth rates (LBRs). A literature review was conducted for all available evidences assessing obstetrics and perinatal outcomes associated with FET compared to fresh ET and natural conception. While studies comparing fresh and FET cycles in normal responders have yielded conflicting results for pregnancy rate, FET was associated with lower risk of prematurity, small for gestational age (SGA), and low birth weight and increased risk of large for gestational (LGA) and/or macrosomic in singletons, when compared with fresh ET. Macrosomic/LGA births have a higher risk of fetal hypoxia, stillbirth, shoulder dystocia, perineal lacerations, cesarean section, postpartum hemorrhage and neonatal metabolic disturbances at birth. Moreover, the risk of high birth weight is probably not the solely increased risk found to be associated with FET. The relative risk of hypertensive disorders in pregnancy, as well as perinatal mortality were also demonstrated to be increased in FET compared with singletons from fresh ET and natural conception. Recent studies have related the aforementioned pregnancy complications to the endometrial priming and not to the cryopreservation process, with higher risk in programmed FET rather than those following natural and stimulated cycles. Thus, when considering elective freeze-all policy, in addition to prematurity, SGA, LBW and the risk of OHSS, physicians should consider the aforementioned increased FET cycles' pregnancy complications. Moreover, FET following natural or stimulated cycles are adviced aiming to reduce adverse outcomes.